1987
DOI: 10.1021/ie00069a012
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of pore surface area during noncatalytic gas-solid reactions. 2. Experimental results and model validation

Abstract: The solid curves in Figure 15 represent the calculated time dependences of unconverted fraction of sulfide by eq 15 and 16. The values of reaction rate constants ki and ku and catalyst fouling parameter 0 were selected so that Literature Cited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 6 publications
6
42
0
Order By: Relevance
“…Based upon our results, we concur that the choice of temperature and reactant gas concentration should have little effect, provided that operation remains under Zone I conditions. Differences in variation of reactivity with burn-off for O 2 and CO 2 have been noted previously [8]. In that earlier study, the patterns exhibited by another Pittsburgh No.…”
Section: Relationship Of Surface Area To Reaction Ratesupporting
confidence: 49%
See 3 more Smart Citations
“…Based upon our results, we concur that the choice of temperature and reactant gas concentration should have little effect, provided that operation remains under Zone I conditions. Differences in variation of reactivity with burn-off for O 2 and CO 2 have been noted previously [8]. In that earlier study, the patterns exhibited by another Pittsburgh No.…”
Section: Relationship Of Surface Area To Reaction Ratesupporting
confidence: 49%
“…The general interpretation is that the surface area for reaction initially increases with burn-off, and then is lost as a result of pore coalescence. In one study [8], the patterns of porosity development were shown to depend upon the combination of reactant gas and char, but were independent of temperature and reactant gas concentration. Based upon our results, we concur that the choice of temperature and reactant gas concentration should have little effect, provided that operation remains under Zone I conditions.…”
Section: Relationship Of Surface Area To Reaction Ratementioning
confidence: 99%
See 2 more Smart Citations
“…The rate of reaction increased gradually between 0 and 70 wt % of gasification and decreased between 70 and 80 wt %. This trend of apparent reaction rate exhibiting a maximum has often been remarked in carbon consumption studies in the literature [32,[44][45][46][47]. Bhatia and Perlmutter [46] and Ballal and Zygouraki [47] explained the maximum rate with the combination of two opposite effects: the augmentation of the reactive surface with pore growth and pore accessibility, and the disappearance of this surface area with pore coalescence and consumption of carbon material.…”
Section: Thermo-gravimetric (Tg) Analysissupporting
confidence: 68%